The Invisible Toolbelt: Exploring the Variety of Language Devices in Effective Teacher’s Talk in Classroom - Hafirah Patang; Reski Yusrini Islamiah Yunus; Wilda Lestari; Ridha Fadillah Rusdin (Universitas Islam Negeri Palopo, 2024)
Teacher’s talk serves as more than a mere medium for instruction. It is a sophisticated pedagogical instrument that dictates the quality of classroom interaction and knowledge construction. This article explores the invisible toolbelt of language devices, ranging from rhetorical strategies and metaphors to pragmatic markers and corrective feedback which is employed by the teachers to facilitate learning. By synthesizing theories of classroom discourse and sociolinguistics, the study examines how these devices function as scaffolding tools that bridge the gap between complex curricula and students comprehension. The analysis highlights that effective teachers do not just speak but strategically manipulate linguistic variables to manage classroom dynamics, stimulate critical thinking, and foster an inclusive rapport. The findings suggest that conscious mastery of these linguistics tools is a critical component of teacher professional development, as it directly impacts the efficacy of instructional delivery and students engagement.